Pollen, Plant Macrofossils, and Insects from Fossil Woodrat (Neotoma Cinerea) Middens in British Columbia - Hebda, Richard; Warner, Barry; Cannings, Robert (Géographie physique et Quaternaire, 1990)
ABSTRACTBushy-tailed woodrats (Neotoma cinerea) occur commonly in cliffs, rock talus, and caves in the open Pseudotsuga menziesii and Pinus ponderosa forests throughout interior British Columbia. Fossil N. cinerea middens from two sites in central British Columbia were radiocarbon dated and examined for pollen, plant macrofossils and insect remains. The Oregon Jack Creek site contains a midden that is dated 1150 ± 80 (WAT-1764) radiocarbon years ago. Pollen analyses reveal an abundance of Cupressaceae (Juniperus) and Pinus. Shrub and herb pollen types include Artemisia. Fabaceae, Poaceae, and Asteraceae. Juniperus scopulorum leaves, Pseudotsuga menziesii needles, Chenopodiaceae seeds. Rosa thorns and Artemisia leaflets are the main plant macrofossils. The remains of three beetle genera, Cryptophagus, Lathridius, and Enicmus represent insects that probably lived in the midden, eating decaying organic matter or moulds. Click beetle (Limonius) remains were probably brought into the midden from nearby soil or plant material. The Bull Canyon site contains a midden that dates to 700 ± 80 (WAT-1765) years BP. Pollen and plant macrofossil assemblages are similar to those at the Oregon Jack Creek site. Woodrat middens offer a new dimension in reconstructing Holocene paleoenvironments in the arid interior of British Columbia, in much the same way as they do in the southwest United States.